Research landscape of glioma and inflammation over the past two decades - Chen, Xiaoli; Wang, Jiabin; Liu, Shiliang; Han, Qingju; Zhang, Haibin; Wu, Jinrong (Frontiers in Immunology, 2025)
IntroductionGlioma is one of the most aggressive brain tumors, and its interaction with inflammation has become an emerging research focus. Despite increasing interest in the role of inflammation in glioma progression and therapy, a comprehensive bibliometric analysis of this field is lacking.MethodsWe conducted a systematic bibliometric analysis of glioma and inflammation research using the Web of Science Core Collection (WoSCC). A total of 4,553 publications from 2005 to 2025 were analyzed for research trends, hotspots, key contributors, and emerging directions using CiteSpace and VOSviewer.ResultsOur analysis revealed a significant increase in publications over the past decade. From 2005 to 2025, a total of 4,553 papers related to glioma and inflammation were published. Key contributing countries, institutions, and authors were identified, highlighting the dominance of the U.S. and China in this field. Leading institutions include MD Anderson Cancer Center and Harvard Medical School (USA) and several top Chinese universities. Keyword clustering and co-citation analysis indicated that expression, growth, and survival are major research hotspots. Highly cited papers primarily focused on molecular subtypes, immune modulation, and therapeutic resistance in glioma. ssGSEA analysis revealed that the score based on the 25-gene signature was significantly enriched in GBM and was closely associated with poor prognosis in GBM patients.ConclusionGlioma and inflammation research have gained increasing attention, particularly in tumor immunity and microenvironment studies. This study outlines the current research landscape and trends, potentially serving as a reference for exploring future areas of investigation and collaboration.